Recently acquired HIV infections and associated factors among men who have sex with men diagnosed at Dutch sexual health centres. (September 2021) - Slurink, Isabel; van Aar, Fleur; Parkkali, Saara; Heijman, Titia; Götz, Hannelore; Kampman, Karlijn; van Weert, Yolanda; van Benthem, Birgit; van de Laar, Thijs; Op de Coul, Eline; ,
Introduction: Surveillance for recent HIV infections was implemented at Dutch sexual health centres (SHCs) for planning and evaluation of HIV prevention initiatives. The study objective is twofold: (1) to explore trends in recent HIV infections and associated socio-demographic and behavioural risk factors among men who have sex with men (MSM )attending SHCs, to gain insight into subgroups at risk for acquiring HIV and(2) to illustrate how comparison with different reference groups affect associations with these risk factors. Methods: Residual plasma or serum samples from MSM newly HIV diagnosed at SHCs in 2014–2017 were tested with an avidity assay. Multinomial regression was used to analyse risk factors for recent HIV infections among MSM with established HIV infections among MSM and with HIV-negative MSM as reference groups. Results: Of newly diagnosed MSM, 33% were classified as recent HIV infection with avidity testing. Combining HIV-negative test results with avidity outcomes resulted in 54% recent infections. Recent infection was associated with having an STI in the past, multiple partners and condom use for both reference groups of MSM. Additionally, relative to the HIV-negative MSM, recent infection was associated with education and having a non-Western origin. In contrast, relative to MSM with established HIV infections, recent infection was associated with Western origin. Conclusion: Our results suggest ongoing but declining transmission of HIV and high uptake of HIV testing among MSM visiting SHCs. The identification of risk factors for recent infections can help healthcare professionals to target subgroups eligible for PrEP or condom use promotion. Differentiation by the reference group in explanatory models for recent infections is important as different risk factors were identified. Likely, associations relative to HIV-negative MSM follow those of acquiring HIV infection in general, whereas the comparison with the established HIV infection reference rather reflects the frequent testing behaviour of subgroups of MSM.